Multiple-factor analysis of dehumidification performance and flow resistance for the cross-flow membrane module based on orthogonal test. Issue 1 (1st August 2022) - Liu, Y L; Su, J C; Cui, X; Yan, W C; Li, N; Jin, L W
Abstract: In this study, the multiple-factor analysis of dehumidification performance and flow resistance for the cross-flow membrane module was carried out based on the orthogonal test. Three operating and four structural parameters were selected as the independent variables for two test indicators, i.e., dehumidification rate ( γ ) and dehumidification account of per unit pressure drop (Δ φ /Δ p ). The influence of seven factors on the test indicators was ranked by the single factor analysis of range. The results indicated that the inlet velocity of humid air, u in, has the most important influence on γ and Δ φ /Δ p . Among the structural parameters of membrane module, the fiber length has the greatest impact on γ while that is the ratio of fiber pitch to fiber outer radius for Δ φ /Δ p . The empirical correlations of γ and Δ φ /Δ p were obtained by the regression analysis of simulated data, which help to predict the dehumidification performance and flow resistance of membrane systems from known structural parameters and operating conditions. According to plus or minus of the fitted exponents, the influences of seven factors on the two indexes are different. The better dehumidification performance and less flow resistance can be achieved by appropriately increasing w in and l of the membrane module. This study is of guiding significance in the structure optimization of membrane modules.